Intrinsic lead ion emissions in zero-dimensional Cs4PbBr6 nanocrystals - Yin, Jun (2020)
We investigate the intrinsic lead ion (Pb2+) emissions in zero-dimensional (0D) perovskite nanocrystals (NCs) using a combination of experimental and theoretical approaches. The temperature-dependent photoluminescence experiments for both “nonemissive” (highly suppressed green emission) and emissive (bright green emission) Cs4PbBr6 NCs show a splitting of emission spectra into high- and low-energy transitions in the ultraviolet (UV) spectral range. In the nonemissive case, we attribute the high-energy UV emission at approximately 350 nm to the allowed optical transition of 3P1 to 1S0 in Pb2+ ions and the low-energy UV emission at approximately 400 nm to the charge-transfer state involved in the 0D NC host lattice (D-state). In the emissive Cs4PbBr6 NCs, in addition to the broad UV emission, we demonstrate that energy transfer occurs from Pb2+ ions to green luminescent centers. The optical phonon modes in Cs4PbBr6 NCs can be assigned to both Pb–Br stretching and rocking motions from density functional theory calculations. Our results address the origin of the dual broadband Pb2+ ion emissions observed in Cs4PbBr6 NCs and provide insights into the mechanism of ionic exciton–optical phonon interactions in these 0D perovskites.